Digital Dialectics and Islamic Education: A Study on the Application of Gemini AI in Mathematics Learning Oriented towards Islamic Values - Renni Juwita Tanjung; Hendri Muliadi; Rajiun Siregar (TATHO: International Journal of Islamic Thought and Sciences, 2026)
This study aims to analyze the integration of Gemini AI in mathematics learning oriented toward Islamic values, drawing on constructivist learning, AI pedagogy, and Islamic moral education perspectives. This study employed a quasi-experimental design using a one-group pretest–posttest approach. The study was conducted through a socialization program involving teachers as participants. Data were collected using questionnaires to measure teachers’ understanding and abilities before and after the intervention. The results indicate a significant improvement in teachers’ understanding of Gemini AI, with the mean score increasing from 2.45 (low category) to 4.12 (high category). In addition, teachers’ ability to integrate AI into learning was categorized as high, with an average score of 3.98, where 76% of teachers were in the high category. The findings indicate that the integration of Gemini AI is associated with increased teacher understanding and perceived ability to implement AI in learning. In addition, teachers reported that AI can facilitate the incorporation of Islamic values such as honesty, responsibility, and justice into instructional contexts. These findings suggest that value-based AI utilization can serve as a strategic innovation in improving learning effectiveness while fostering students’ character development.